Identifying patients at risk of inhospital death or hospice transfer for early goals of care discussions in a US referral center: the HELPS model derived from retrospective data. Issue 1 (21st January 2018) - Romero-Brufau, Santiago; Whitford, Daniel; Whitford, Kevin J; Manning, Dennis M; Huddleston, Jeanne M
Abstract : Objective: Create a score to identify patients at risk of death or hospice placement who may benefit from goals of care discussion earlier in the hospitalisation. Design: Retrospective cohort study to develop a risk index using multivariable logistic regression. Setting: Two tertiary care hospitals in Southeastern Minnesota. Participants: 92 879 adult general care admissions (50% male, average age 60 years). Primary and secondary outcome measures: Our outcome measure was an aggregate of inhospital death or discharge to hospice. Predictor variables for the model encompassed comorbidities, nutrition status, functional status, demographics, fall risk, mental status, Charlson Comorbidity Index and acuity of illness on admission. Resuscitation status, race, geographic area of residence and marital status were added as covariates to account for confounding. Results: Inhospital mortality and discharge to hospice were rare, with incidences of 1.2% and 0.8%, respectively. The Hospital End-of-Life Prognostic Score (HELPS) demonstrated good discrimination (C-statistic=0.866 in derivation set and 0.834 in validation set). The patients with the highest 5% of scores had an 8% risk of the outcome measure, relative risk 12.9 (10.9–15.4) when compared to the bottom 95%. Conclusions: HELPS is able to identify patients with a high risk of inhospital death or need for hospice at discharge. These patients may benefit from early goals of care discussions.